(untitled) (Journal of Misan Researches, 2020)
The Turkish –lsraeli agreement in 1996 in considered one of the important and influential strategic changes in the middle east ,because it was largely consistent with turkeys interests and the fulfillment of Israel strategies in the region while lran found in it a threat its national security ,and its great interests in central Asia especially in Azerbaijan .moreover, it granted a privilege to Israel to be present on the Iranian borders and to threaten it. Based on these facts lran was forced to increase its military and defense expenditures to counter these threats.